The Interaction Analysis of SNP Variants and DNA Methylation Identifies Novel Methylated Pathogenesis Genes in Congenital Heart Diseases - Wang, Jing; Ma, Xiaoqin; Zhang, Qi; Chen, Yinghui; Wu, Dan; Zhao, Pengjun; Yu, Yu (Frontiers in Cell and Developmental Biology, 2021)
Congenital heart defect (CHD) is a rare and complicated disease with a high mortality rate. It’s etiology still remains unclear and includes many aspects. DNA methylation has been indicated to be involved in heart development in the early stage of life, and aberrant methylation level was related to congenital heart defects. This study provides the first evidence that the cross talk of SNP variants and DNA methylation in clarifying CHD underlying genomic cause. We performed Group1 for whole exome sequencing (WES) data consisting of patients with PA (n=78), TOF (n=20), TAPVC (n=78), PDA (n=40) and 100 healthy children as the control group. Rare nonsynonymous mutations and novel genes were found and highlighted. Meanwhile, we carried out the second analysis of DNA methylation data from PA (n=3), TAPVC (n=3), TOF (n=3), PDA (n=2) and 5 healthy controls using 850K array in Group 2. DNA methylation was linked with WES data and we explored an obvious overlap of hyper/hypomethylated genes. Next, we identified some candidate genes by Fisher’s exact test and Burden analysis, then those methylated genes were figured out by the criterions of the mutation located in the CpG islands of the genome, differential methylation sites and DNA methylation quantitative trait loci (meQTLs) in the database, respectively. Also, the interaction of differentially methylated candidate genes with known CHD pathogenetic genes was depicted in a molecular network. Taken together, our findings show that 9 novel genes （ANGPTL4, VEGFA, PAX3, MUC4, HLA-DRB1, TJP2，BCR, PKD1 and HK2）in methylation level were critical to CHD, and reveal a new insight into the molecular pathogenesis of CHD.